UPAYA UNTUK MENGEMBANGKAN KETERAMPILAN MOTORIK HALUS MELALUI AKTIVITAS ORIGAMI DENGAN METODE DEMONSTRASI PADA ANAK-ANAK KELOMPOK B DI TK BINA NUSANTARA - Febri Valentina; Esa Wulandari; Lenny Nuraeni (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
This research is based on the main problem that is about: "How to Develop fine motor skills through origami activities with demonstration method in child group B in kindergarten Bina Nusantara".Theoretical basis used in this study include: Early Childhood Concepts of Education, Concept of Motor Development, Concept Origami.Konsep Demonstration Method.The method used in this research is qualitative with descriptive method. This study intends to obtain empirical data on how to develop fine motor skills through origami activities with demonstration methods in group B children in kindergarten Bina Nusantara. The authors define the method used in this study is descriptive method with the consideration that this method is a way of research by describing events that exist in the present or that is happening, so to achieve the purpose of this study using a qualitative approach while the instrument used in this study is interviews, observations, documentation studies, and literature studies conducted to one principal, two managers, and three educators.In this action research the researcher performs the action through origami activities.